An investigation of equine hoof shapes using physical descriptors from micro-computed tomography - Taylor, Sophie (2017)
Reasons for performing the study: As the most common cause of equine euthanasia, equine foot lameness is highly prevalent thus having high economic and welfare impacts. Those of particular concern are foot pathologies associated with the lamellae, more commonly known as ‘laminitis’. To investigate the full extent of the equine foot in order to gain a sufficient understanding of its anatomical structures in a normal state and the pathological adaptations associated with laminitis, a novel technique was employed with the utilization of micro-computed tomography. Aims and objectives: The aim of this study was to investigate the anatomical components of the equine foot with the use of a laboratory μ-CT scanner. The fundamental objective underpinning this study was to mathematically model the different physical descriptors of the equine foot and their morphological state. Methods: 44 cadaveric equine feet μ-CT image stacks were used to assess their anatomical components with the use of Fiji ImageJ software. 44 equine feet were used to calculate the dorsal hoof wall curvature and dorsal hoof wall thickness at the quarters and 43 at the toe region. The third phalanx (P3) was analysed by calculating its dorsal curvature (n=43), cortical bone thickness (n=44) and trabecular bone anisotropy (n=44). Analysis of the vasculature network was calculated in 28 equine feet, recording the total branch lengths, mean lumen diameter and the percentage of stretched to bundled vessels. In addition, the corium volume was calculated for a total of 44 equine feet. The data was mapped as a function of dorsal hoof wall curvature, bone curvature and categorised using both variables. The percentage of stretched to bundled vessels and vasculature volume was also plotted as a function of corium volume. Results: Hoof capsule and P3 curvature measurements differed between feet, calculated using a modified version of the differential calculus equation. From these measurements four different morphological categories were established for comparison against other physical descriptors. Dorsal hoof wall thickness was measured and found to be thicker at the quarters than at the toe region irrespective of dorsal hoof curvature. Changes in P3 curvature, trabecular bone anisotropy at the toe tip and cortical bone thickness occurred more frequently in feet with a convex dorsal hoof wall. No significant changes to the blood vessels were identified. However vasculature volume and corium volume increased almost linearly with respect to one another (P<0.001). A greater percentage of bundled vessels were shown in feet with a convex dorsal hoof wall and dorsal P3 surface. Conclusions: This study demonstrates how the novel application of μ-CT scanning can be used to investigate the anatomical components of the equine foot. Furthermore measurements and data can be extracted from these images enabling the physical descriptors to be mathematically modelled for analysis. Potential relevance: Despite extensive research, the pathogenesis and pathomorphology of laminitis has not been explained. With the application of μ-CT the identification of anatomical adaptations in equine feet with foot pathologies could assist in this understanding.